Effect of Ti alloying in nickel silicide formation - Setiawan, Y. (2013)
In the presence of interfacial oxide, an addition of 20 at.% Ti to Ni film leads to the formation of a thick TiOx layer at the Ni(Ti)/Si interface upon annealing, preventing the inter-diffusion of Ni and Si hence hindering the Ni silicide formation up to 700 °C. At 800 °C, a mixture of predominant NiSi phase with some NiSi2 grains facetted in (111) plane was observed. A different mechanism occurred for the sample with minimal oxygen contamination where Ni3Si2 was found to be stable up to 900 °C. Nevertheless, Ti addition has delayed the silicidation reaction to 600 °C.